Protective effect of glucosinolates hydrolytic products in neurodegenerative diseases (NDDs) - Sani, Mohammed Jaafaru; Abd Karim, Nurul Ashikin; Mohamad Eliaser, Enas; Rollin, Patrick; Mazzon, Emanuela; Abdull Razis, Ahmad Faizal (MDPI, 2018)
Crucifer vegetables, Brassicaceae and other species of the order Brassicales, e.g., Moringaceae that are commonly consumed as spice and food, have been reported to have potential benefits for the treatment and prevention of several health disorders. Though epidemiologically inconclusive, investigations have shown that consumption of those vegetables may result in reducing and preventing the risks associated with neurodegenerative disease development and may also exert other biological protections in humans. The neuroprotective effects of these vegetables have been ascribed to their secondary metabolites, glucosinolates (GLs), and their related hydrolytic products, isothiocyanates (ITCs) that are largely investigated for their various medicinal effects. Extensive pre-clinical studies have revealed more than a few molecular mechanisms of action elucidating multiple biological effects of GLs hydrolytic products. This review summarizes the most significant and up-to-date in vitro and in vivo neuroprotective actions of sulforaphane (SFN), moringin (MG), phenethyl isothiocyanate (PEITC), 6-(methylsulfinyl) hexyl isothiocyanate (6-MSITC) and erucin (ER) in neurodegenerative diseases.